Distributed system of low-consumption sensors to monitor environmental variables in indoor spaces - Palacios, Oliver; Plaza Vargas, Angel Marcel; Lino Castillo, Katty Nancy (EASI: Engineering and Applied Sciences in Industry, 2022)
Currently, the analysis of air quality and environmental conditionsin indoor environments have been an important subject of study, becausepeople spend most of the day in closed places, such as buildings, houses,classrooms, offices, etc. This article describes the development of aprototype of a distributed network of environmental sensors, which areresponsible for measuring the environmental variables of humidity andtemperature, with efficient sensors, low cost and low energy consumption.This system allows monitoring three different points within a differentenvironmental setting, located in strategic places, thus obtaining a differentsample. The prototypes capture the measurements of the environmentalvariables and register them in a database contained in a web server to laterbe presented to the end user. These measurements are made and displayed inreal time.
Keywords: distributed network; environmental sensors; humidity; temperature; data base